Literary criticism from Plato to postmodernism the humanistic alternative - Seaton, James 1944- (New York Cambridge University Press, 2014)
"This book offers a history of literary criticism from Plato to the present, arguing that this history can best be seen as a dialogue among three traditions - the Platonic, Neoplatonic, and the humanistic, originated by Aristotle. There are many histories of literary criticism, but this is the first to clarify our understanding of the many seemingly incommensurable approaches employed over the centuries by reference to the three traditions. Making its case by careful analyses of individual critics, the book argues for the relevance of the humanistic tradition in the twenty-first century and beyond"--Provided by publisher.
Machine generated contents note: Introduction; 1. Plato and neoplatonism; 2. Romanticism and modernism; 3. Theory and cultural studies; 4. Aristotle and the humanistic tradition; 5. Edmund Wilson and Lionel Trilling; 6. Democracy, popular culture, and Ralph Ellison; 7. Literary criticism, the humanities, and liberal education.
Includes bibliographical references (pages 199-214) and index.
Keywords: Criticism -- History; Literature -- Philosophy